Il pas di Derrida fra decostruzione e psicoanalisi - D’Aurizio, Claudio (Bollettino Filosofico, 2021)
This paper follows some traces of a problem that often emerges in Jacques Derrida’s works: the relation between the devil and psychoanalysis. Many references to this connection appear in his texts, even if they have not been explored by Derrida’s readers yet. The Post Card. From Socrates to Freud and Beyond (1980) is the main text of this investigation, as this book introduces two conceptual figures that often return in Derrida’s deconstruction. The first one is the step, which refers both to the devil’s limping and to Freud’s speculation in Beyond the Pleasure Principle (1920). The second one is the expression “devil’s advocate”, used by Freud in the same text to present and justify his theoretical discoveries. This article claims that both these figures hide a deep connection with Derrida’s conception of deconstruction. Keywords: Deconstruction, Derrida, Fort/da, Freud, Psychoanalysis